Strategic analysis of the 2014 Wounded Warrior Project annual alumni survey : a way forward - Cerully, Jennifer L.; Smith, Meagan; Wilks, Asa; Giglio, Kate (Research report (Rand Corporation) ;, 2015)
"Wounded Warrior Project® (WWP) provides support and raises public awareness for service members and veterans who incurred physical or mental injury, illness, or wound coincident to their military service on or after September 11, 2001, as well as their families and caregivers. Through WWP, members (Alumni) have access to programs that support four main areas of recovery -- engagement, mind, body, and economic empowerment. Using 2014 WWP Annual Alumni Survey data, RAND researchers offer a detailed analysis of how Alumni of different genders, races and ethnicities, military service histories, and service-related health conditions fare in terms of mental health, physical health, and economic well-being. The report also offers recommendations for the organization's decisionmakers to consider in setting goals and creating programs to support WWP Alumni"--Publisher's web site